(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Medical education has undergone drastic changes by including new teaching methodologies with the inclusion of online reading portals along with textbooks. This study aimed to assess the studying resources opted by undergraduate medical students and the impact on their academic grades. Subjects and methods: This cross sectional survey was conducted at Liaquat National Hospital and Medical College, Karachi, Pakistan from April to July, 2018. A total of 299 undergraduate medical students were recruited through purposive sampling technique. A self-administered structured questionnaire was developed for data collection. The grades obtained by the students during recent module exams were utilized for this study. These grades were then correlated with independent factors like studying resources opted by the students. SPSS version 22 was used for data entry and analysis. Results: The students used textbooks and the internet for their studies, instead of one resource alone. YouTube was the most commonly accessed website. There were significant associations between the combined use of textbooks as well as internet and higher academic grades. Females and junior students were also significant predictors of better exam grades, although there was no difference in their studying resources. Conclusion: The study highlighted the importance of the combined use of textbooks and internet as most useful in the attainment of better exam grades in medical education. Further experimental studies are required in order to study in detail regarding the various other factors impacting the grades of a student, apart from reading resources.